Ceftazidime-related urinary calculi in a young boy: a case report - Gao, Pan (J Int Med Res, 2020)
Certain drugs can cause kidney stones but as far as we are aware, ceftazidime-related urinary calculi have not been previously reported. We report here a case of an 8-year-old boy who developed hydronephrosis secondary to urinary calculi after receiving ceftazidime 2.0 g by intravenous infusion daily for two weeks. Previously, his left kidney showed no signs of disease. A retrograde double J ureteral stent was inserted, ceftazidime terminated, fluids increased and urine alkalised. On day 25, the patient showed no signs of kidney stones or hydronephrosis. Clinicians should be aware of the possibility of ceftazidime-related urinary calculi particularly if patients are receiving long-term treatment.